Siedlung und Städtebau im Küstengebiet des alten Peru - Trimborn, Hermann (ERDKUNDE, 1968)
More so than in the Andean Highland, urbanism was an element in the early cultures of the Peruvian coastal zone. Its origins go back to the 1st millenium B. C. Urban growth occured in the 1st millenium A. D. primarily in ceremonial centres, while late pre-Columbian times are distinguished by the development of profane towns and cities. Inbetween are transition forms, characteristic of the centuries of the Tiahuanaco expansion. It is only in recent years that researchers, particularly Americans, have paid more attention to urbanisation. They have concerned themselves not only with the indicated typological questions but also with the varying geo graphic locations and, in this connection, the possibilities of towns existing through irrigation systems. The problems of urbanisation call for further study of the three co-ordinates of geographic location, temporal phases and socio economic function. These studies include the important question of the southern boundary of High Culture development in the coastland. This question can probably only be answered in a fragmentary fashion, for individual epochs and according to whether one is considering only urbanism or the spread of mobile cultural equipment.